Tardigrade and Manifold Sign: Two New Signs in Dupuytren's Disease - Reyntiens, Pieter; Vanhoenacker, Filip M.; Jager, Tjeerd (Seminars in Musculoskeletal Radiology, 2023)
Dupuytren's disease (DD) is a chronic benign fibroproliferative disorder of the palmar and digital fasciae. It is characterized by formation of nodules and fibrous cords that may eventually lead to contractures with permanent flexion of the finger joints. Correction of the flexion contractures in advanced disease is still performed by open limited fasciectomy; ultrasonography (US)-guided minimally invasive treatment is preferred for early disease.We provide an overview of the detailed anatomy of the palmar aponeurosis and the structures that may be involved in DD. Although magnetic resonance imaging is used as the gold standard, these small anatomical structures are often better visible on US. We describe two new morphological signs due to thickening of these small structures in patients with DD: the tardigradesign and the manifoldsign.Familiarity with detailed imaging anatomy and these new imaging signs of DD will help confirm a correct and early diagnosis and distinguish this disease from various other entities.
Keywords: Dupuytren's disease; imaging anatomy; palmar fascia; tardigrade sign; manifold sign